A STUDY OF IDIOMS CONTAINING WORDS DENOTING HUMAN COMMON SHELTERS (ENGLISH VERSUS VIETNAMESE) - Trần Ngọc Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Learners of every language always have problems with idiom, the special brand of a language. It is not difficult because of the linguistic elements used inside, but because people cannot understand it correctly with only the knowledge of that target language. In fact, they also have to provide themselves with a lot of cultural knowledge in order to get the meanings of idioms. Each country has its own culture and no two countries have exactly the same culture as the other. It also happens to idioms of different languages. Although they share some common ground, English idioms and Vietnamese idioms differ greatly due to cultural differences. In this thesis, English and Vietnamese idioms containing words denoting human common shelters are studied in terms of syntactic and semantic features to figure out the similarities and differences between the two languages. In the thesis, 62 English idiom samples and 49 Vietnamese idiom samples containing words denoting human common shelters are investigated. All the samples, together with numerous of examples from various linguistic books, dictionaries, short stories and the Internet, are taken into consideration and fully studied. The findings show that not only idioms containing words denoting human common shelters have remarkable syntactic and semantic features and there are interesting similarities and differences between English and Vietnamese. This thesis also deals with the implications for teaching and learning English as a foreign language in Vietnam. It can help teachers and students of English a lot. Moreover, it can also be used for further study.